Early Christianity in Asia Minor and Cyprus: from the margins to the mainstream - Mitchell, Stephen; Pilhofer, Philipp (Early Christianity in Asia Minor (ECAM), 2019)
"This volume is part of the Berlin TOPOI project re-examing the early Christian history of Asia Minor, Greece and the South Balkans, and is concerned with the emergence of Christianity in Asia Minor and in Cyprus. Five papers focus on the east Anatolian provinces, including a comprehensive evaluation of early Christianity in Cappadocia, a comparative study of the Christian poetry of Gregory of Nazianzus and his anonymous epigraphic contemporaries and three essays which pay special attention to the hagiography of Cappadocia and Armenia Minor. The remaining papers include a new analysis of the role of Constantinople in episcopal elections across Asia Minor, a detailed appraisal of the archaeological evidence from Sagalassos in Pisidia, discussion of the significance of inscriptions in Carian sanctuaries through late antiquity, and a survey of Christian inscriptions from Cyprus